Response analysis of hollow core slab bridge with different column heights to near-fault seismic motions. - Sayed Mahmoud; Ahmed Soliman; ‪magdy GENIDI; Waleed Abdallah (JES: Journal of Engineering Sciences)
The near-fault earthquake motions are characterized by influential velocity impulses, and remarkable permanent displacement. Such unique characteristics can substantially change the induced seismic responses of structures. The current study incorporates near-fault earthquake motions with forward-directivity and fling-step to excite a reinforced concrete (RC) hollow-core slab bridge with varying column heights. The study adopts a RC hollow-core slab bridge having three spans, each 30.0 m long, with a deck width of 11.5 m, a depth of 2.0 m and column’s heights designed to meet a span-to-column height ratio of 2.5 to 5. Three-dimensional numerical models of the bridge are established using the CSI-BRIDGE software and dynamic time-history analysis is used to capture the simultaneous influence of near-fault motions and supporting columns with varying heights on the seismic response of the RC hollow-core slab bridge, under selected earthquake loads. Upon analyzing the seismic response of the excited bridge, the simulation results revealed that substantial increase in seismic demands of the bridge with more susceptibility to near-fault motions with fling-step than the forward directivity ground motions. This effect is more pronounced for bridge models with taller columns than models with reduced column’s height.